Designing Computational Grids Using Best Practices in Software Architecture - Prem, Hema; Raghavan, N.R. Srinivasa (Universiti Utara Malaysia Press, 2010)
The basic principle of sharing and collaborative work by geographically separated computers is known by several names such as meta computing, scalable computing, cluster computing, internet computing and this has today metamorphosed into a new term known as grid computing. Grid computing is proving to be promising method of HPC, which is packaged with many challenges. This paper elucidates the role that pattern can play in architecting complex systems with specific reference to grid computing. We provide descriptions of a set of well-engineered patterns that the practicing developer can apply to crafting his or her own specific applications. We develop the Software Requirements Specification (SRS), with an attempt to drive to effectual design specifications for use by any grid developer. We analyze the grid using an Object Oriented approach and present the design using the unified Modeling Language (UML) which itself helps the identification of patterns at different phases.